GRAPE JUICE MINIMIZES INFLAMMATION AND REDUCES HOSPITALIZATION TIME IN PATIENTS WITH COVID-19 - de Moura Costa, Crislane; Sergio Silva, Alexandre; Pereira de Sousa, Aislan Erick; Carvalho de Moura, Rayane; Oliveira Silvino, Valmir; Camarão Telles Biasoto, Aline; Santos Lula Barros, Débora; Lustosa Barros, Esmeralda Maria; da Rocha Sousa, Leonardo; Lopes Macedo, Joyce; et al. (Revista Interfaces: Saúde, Humanas e Tecnologia, 2025)
Inflammation and oxidative stress are the main mortality mechanisms caused by SARS-CoV-19. Grape juice has anti-inflammatory and antioxidant properties, which are believed to be beneficial in treating COVID-19. This randomized clinical trial evaluated the impact of grape juice supplementation in the treatment of patients with COVID-19. Thirty-six patients were randomized to the grape juice supplementation group (GJG, n = 20; 10 ml/kg/day) or the control group (CG, n = 16), which received conventional COVID-19 treatment protocols. Blood samples were collected at admission and discharge for analysis of oxidative stress markers. CBC, C-reactive protein levels, electrolytes and markers of renal function were obtained from medical records. Handgrip strength was also measured to assess muscle strength. The GJG presented significantly lower levels of C-reactive protein compared to the CG (16.35 ± 26.81 vs 56.51 ± 73.29, respectively) with an intragroup decrease in C-reactive protein after the procedures (p = 0.010). The strength of the non-dominant hand in the GJG improved in relation to pre-intervention levels and in the CG after the procedures (p < 0.05), there was a significantly shorter time of hospitalization for the GJG compared to the CG (6.85 ± 3.16 vs 9.94 ± 5.69 days, respectively). The addition of grape juice during COVID-19 treatment reduced inflammation levels and length of hospital stay, as well as increased upper limb functional strength in COVID-19 patients. Clinical trial registration: RBR-4bcp54k